Pro ASP.NET MVC 2 Framework - Sanderson, Steven (Apress, 2012)
This book is for professional software developers who already have a working understanding of C# and general web development concepts such as HTML and HTTP. Many readers will have background knowledge of traditional ASP.NET (now known as Web Forms, to distinguish it from MVC), so in many places I point out the similarities of and differences between the two ASP.NET technologies. But if you’ve used PHP, Rails, or another web development platform, that’s fine too. To get this most out of this book, you’ll need to have a fair level of passion and enthusiasm for your craft. I hope you’re not satisfied just to throw together any old code that appears at first to work, but instead would prefer to hone your skills by learning the design patterns, goals, and principles underpinning ASP.NET MVC. This book frequently compares your architectural options, aspiring to help you create the highest quality, most robust, simple, and maintainable code possible.